Fake truth [compact disc, unabridged] - Goldberg, Lee, 1962- (Goldberg, Lee, 1962- Ian Ludlow, 2019)
Author Ian Ludlow writes great adventures ... but after helping Chinese movie star Wang Mei defect to the United States, he becomes the accidental hero of a real-life espionage thriller. Now he's stuck with the actress--and suffering a nasty case of writer's block--when he stumbles into a secret Russian plot using "fake news" to outrage Americans into believing a terrifying lie.